PERMUKIMAN KEMBALI PASCA BENCANA TSUNAMI DI DESA KUALA BUBON KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - , Zulfiadi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Post-tsunami settlement object in the village of Kuala Bubon is previously a residential area where completely destroyed by the tsunami and has been reorganized again. They cannot live in a relocation village inland and prefer living close to the coastal again even though the area was prone to tsunami. This study aims to describe and to review the concept of living in post-tsunami resettlement in coastal communities. This research was conducted using qualitative inductive research with phenomenological approach. Sources of data obtained through observation, in-depth interviews with in coastal communities, and secondary data from various related institutions. Descriptive analysis was conducted to obtain keywords which are then bitted into the themes and resulted local concepts. The study found that the presence of the concept of living \"Aneuk-aneuk Pinyi tetap Udep bak laot\" that means that coastal communities can only live peacefully near the sea as a source of natural marine life. Choice of living in coastal communities cannot be separated from local wisdom in the context of marine customary laws it can be observed from implementation of marine customary laws, traditional institutions, customary sanctions, and also local knowledge related to nature performance such as building elevation planning, time to work at sea, searching for shrimp cages in rivers and efforts associated with the tide. This resettlement due to the similarity of their livelihood characteristics, social relationships, strong kinship, ensuring the necessities of life and business, parents/ family relationship and love of the homeland. The study also found a shift in people's behavior after resettlement, this activity happens due to low resources management and poor condition in the rural area.